Board Capital, Board Independence, and Bank Risk-Taking: The Case of a Small Emerging Country - Ramly, Zulkufly (Animo Repository, 2022)
This study investigates the effect of board capital on commercial bank risk-taking, and the moderating effect of board independence in commercial bank risk-taking. This study extends prior literature by integrating the resource dependence and agency theories in examining the specific attributes of board capital and board independence and their effect on risk- taking. Data from eight Malaysian commercial banks from 2002 to 2014 were analyzed using generalized least squares (GLS) panel data regression technique to estimate the effect of board capital and moderating effect of board independence on bank risk-taking. The board capital data is hand-collected from the bank annual reports. The financial data is obtained from Bankscope. Directors’ experience in risk management, high status, and political connection significantly affect bank risk-taking and the effect is non-linear. Board independence moderates the relationship between the board capital and risk- taking. The findings suggest that it is not sufficient to just focus on the board independence because the directors’ ability to perform monitoring and advisory roles vary, depending on human and social capital resources they bring to the board. Thus, the contribution of the board oversight role should be evaluated in combination with the board capital. The findings are useful for the board of commercial banks and regulatory bodies to strengthen the board oversight role in risk-taking and enhance board diversity. This research highlights how board composition can be configured to control risk-taking in terms of the extent of its independence and the specific attributes board capital. The finding reaffirms the integration of the resource dependence and agency theory perspectives in corporate governance research. To the best of our knowledge, this study is a preliminary attempt to explore the value of board capital and its interaction with board independence in banking institutions in affecting risk-taking based on the integration of resource dependence and agency theories.